Visual Narratives: Video on a YouTube Channel as an Instrument of Socio-Political Activism - Ait Hadi, Khalid; Amadane, Rachid; Bendahan, Mohamed (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
This article studies the transformative role of videos as a multifunctional tool in socio-political activism, with a focus on a Moroccan YouTube channel. It demonstrates how visual narratives are not only vectors of information but can become active participants in redefining power dynamics and engagement in public spaces. Through an analysis of contents and their impact, the study highlights how videos contribute to the emergence of new political discourses, put into question mainstream narratives. The article further examines the ability of videos to politicize events, spark debates and incite to collective action, highlighting their potential as powerful tools of mobilization.